Central Bank Digital Currency and Financial Stability in Indonesia: Analysis on Vector Error Correction Model (VECM) Approach - Enggarwati, Mutia; Puspitasari, Inda Fresti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Introduction/Main Objectives: Central Bank Digital Currency (CBDC) is an electronic form of banknotes, but different from virtual currency or cryptocurrency which are not issued by the state, the CBDC issued and guaranteed by the central bank. The aim of this study is to investigate the impacts of CBDC on financial stability using a Vector Auto-regressive model. The endogenous variables in the VAR estimation contain the Central Bank Digital Currency Attention Index (CBDCA), composite stock price index, real exchange rate, and interest rate (BI7DRR). Background Problems: The presence of CBDC will change the objective of Bank Indonesia and influence the structure of the monetary policy, which is no longer focused on achieving a low and stable inflation rate but on achieving price stability. Novelty: Although CBDCs will be launched worldwide, there are a limited number of empirical studies that have analyzed their impact on financial stability, especially for the case study in Indonesia. In this paper, we also use the Vector Error Correction Model (VECM) model with stochastic volatility and Impulse Response Function to make a forecast and see the impacts of shocks on the financial variables. Research Methods: In this study, we used monthly time series data from January 2019 – January 2023. In order to find the correlation between CBDC and the financial market we used the Granger causality model and impulse response function analysis. Finding/Results: The results of this study prove that CBDC has a positive correlation with the real exchange rate, and financial markets such as stock or bond prices have a positive response to shocks in CBDC. Conclusion: In this study, we used monthly time series data from January 2019 – January 2023. We use empirical tests to examine the CBDC attention index in relation to index attention, exchange rates, interest rates and IHSG. Our empirical results show that in Granger causality there is no causal relationship between CBDC and other macroeconomic variables. whereas in the IRF analysis, the response to the CBDC shock tends to be stagnant, the FEVD results show short-term and long-term shock fluctuations in the CBDC and other variables. These results indicate that CBDC does not have a significant effect on the macroeconomic variables used as indicators of financial system stability, but on the contrary, people's attention to CBDC depends on the condition of the variables in the financial system. On the other hand, the development of CBDC depends on economic conditions. The uncertainty surrounding CBDC plays an important role in indicating that the introduction of CBDC brings significant changes to the economy.